FACTOR ANALYSIS ON THE EFFECTIVENESS OF MANAGEMENT OF STATE AND REGIONAL PROPERTY - Firdaus, Luthfandi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
The main objective of this study is to examine factors affecting the effectiveness of state and regional property management. This is a descriptive study that discusses the effectiveness of state and regional property management through a factor analysis. The data for this study were gathered through a survey of the literature. The factor analysis of this research data identifies five categories of factors: security and maintenance of state property, planning and administration of state property, use of state property, and technical guidance for state property. While the planning factor - purchase of BMD - is prominent in the management of regional property, the usage factor - utilization of BMD - is also significant. This is because planning is critical for facilitating the control and supervision processes. Meanwhile, utilization and use might be considered effective if they are accompanied by proper management and periodic maintenance.